Corporate Governance Mechanism – Financial Performance Nexus : Empirical Evidence from Indian Banks - Singh, Raj Kumar; Sharma, Munish; Kumar, Ajay; Singh, Yashvardhan (Indian Journal of Finance, 2022)
This study empirically analyzed the corporate governance mechanism – financial performance nexus of banks in India. The analysis was based on balanced panel data over the period from 2010 – 11 to 2020 – 21 for 10 public and private sector banks, using a hierarchical multiple regression approach. The study investigated the three aspects of financial performance, namely return on assets, return on equity, and Tobin’s Q ratio. Based on previous studies, a conceptual model was developed by taking the financial performance of banks as a dependent variable, corporate governance attributes as independent variables, and age, size, growth, and financial leverage as control variables. Content analysis was applied to derive the Corporate Governance Index. The findings for accounting-based measures revealed that board attendance had a positive and significant impact on ROA and ROE of banks, while board expertise and CEO duality had a negative and significant impact on ROA and ROE. Moreover, board gender diversity had a positive and significant impact on ROE, and board committees had a negative and significant impact on ROE. A study for market-based measures found that board meetings had a positive and significant impact on TQR, whilst board committees and board expertise had a negative and significant impact on TQR. The study’s outcomes implied that banks, government, regulators, and policymakers should ensure and promote strong corporate governance mechanisms to compete in the global financial market.